Efficiency of polymer materials in highly loaded systems in the aviation industry - Anita Ptak; Tadeusz Leśniewski; Michał Purzycki; Krzysztof Płonka (Aviation, 2023)
The static coefficient of friction was calculated on an inclined plane tribological stand. Different specimens and masses loading the system were used during the experiment. Surface-to-surface contact was tested in a pin-on-plate setup. The tested polymer pairs were POM on POM, PA6 on PA6 and PET on PET. The variables in the experiment were different pressures acting on the friction pair, and dry and lubricated friction was tested. Static coefficients of friction for each case was calculated and the surface quality of the pin and plate was measured by profilometer and optical microscope. The coefficient of static friction was higher for lubrication friction than the dry friction. It was also observed that the coefficient of friction decreases with increased load. POM – POM pair had the lowest coefficient of friction under dry conditions, while for lubricated friction, PA6 – PA6 had the most stable increase of friction coefficient.